The utility of Drosophila melanogaster as a fungal infection model - Mpamhanga, Chengetai D.; Kounatidis, Ilias (Frontiers in Immunology, 2024)
Invasive fungal diseases have profound effects upon human health and are on increase globally. The World Health Organization (WHO) in 2022 published the fungal priority list calling for improved public health interventions and advance research. Drosophila melanogaster presents an excellent model system to dissect host-pathogen interactions and has been proved valuable to study immunopathogenesis of fungal diseases. In this review we highlight the recent advances in fungal-Drosophila interplay with an emphasis on the recently published WHO’s fungal priority list and we focus on available tools and technologies.